Do not take risks (Revista Venezolana de Salud Pública, 2020)
At present, Venezuela has around 400 daily cases of infected people diagnosed by Covid 19, for a total of 93,921 positive cases and 819 deaths until November 5, a figure that increases day by day. The number of cases is probably higher but we know the underreporting that exists in the country due to the lack of an adequate epidemiological surveillance mechanism and in addition to the lack of a sufficient number of rapid tests and PCR to diagnose this disease.